Obstetric and neonatal outcome among women presenting with reduced fetal movements in third trimester - Poojari, Vidyashree G.; Kumar, Sahan S.; Vasudeva, Akhila (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Reduced maternal perception of fetal movements allows early identification, timely evaluation and intervention for fetuses at risk of adverse outcome. The primary objective of this study was to assess the pregnancy characteristics and outcomes of pregnant women presenting to hospital with reduced fetal movements (RFM). Methods: Prospective observational study, recruiting all women with singleton pregnancy at or beyond 28 weeks of gestation presenting with a subjective perception of RFM from April 2015 to December 2016. Maternal characteristics, antenatal risk factors, management pathways and perinatal outcome studied. Results: 47% belonged to high risk pregnancy. Among high risk women, although only 39% showed poor BPP at the first presentation, 58% were delivered irrespective of their gestational age, out of which 32.75% had poor neonatal outcome. Among low risk who had >2 episodes of RFM, 50% had poor neonatal outcome. 7% among high risk pregnancies and 18% among low risk, presented with RFM within 48 hours following steroid prophylaxis.24% of high risk women showed liquor volume abnormalities as compared to low risk (6.3%). Conclusions: Significant proportion of those with RFM belonged to high risk pregnancy. Among high risk group, there were high rates of stillbirth and poor BPP at the time of admission when compared to low risk group. Due to early approach to the hospital and timely intervention, significant women with abnormal BPP had good perinatal outcome. All those fetuses who were delivered on first episode of RFM in low risk group did not show evidence of compromise at birth, probably indicating unnecessary delivery. More than 2 episodes of RFM even among low risk group seems significant as good number of fetuses were compromised at birth. Steroids prophylaxis for the fetal lung maturity causes transient changes in BPP, hence unnecessary delivery should be avoided especially those among low risk pregnancy.